Research and analysis of environmental legal compensation mechanisms related to waste incineration in the context of “double carbon” - Gao, Yuanfei; Gao, Ruosu (Frontiers in Ecology and Evolution, 2022)
In the context of "double carbon", waste disposal has become a key issue so far, and how to deal with it is the key to ensure compliance with the double carbon target, the most practical treatment is still incineration, and how to establish the site selection and legal compensation mechanism is crucial.This paper establishes an environmental dynamic monitoring system for waste incineration power plants based on Gaussian model, and successfully solves the health risk of surrounding residents. Regarding the economic compensation issues we first applied the AHP to comprehensively analyze the pollutants, constructed the judgment matrix and conducted consistency test, determined the weight of each index, and integrated various emissions into one pollutant, which is convenient for the concentration of pollutants. Then, by taking into account the effects of wind direction, rainfall, topography and other factors on the diffusion of pollutants, we calculated the pollutants around the site of the waste incineration power plant based on the “elevated continuous point source diffusion model”. To obtain the concentration distribution, monitoring points were set up at representative locations, and the environmental monitoring system of waste incineration power plant was established. Finally, Matlab software was used to draw the contour map of pollutant concentration, and the concentration level of pollutants was divided according to waste incineration. In view of the income of the power plant, the economic level of the surrounding residents, the amount of compensation from the local government, and the pollution level, economic compensation plans for the surrounding residents were developed. Through analyzing the proposed compensation scheme, it can be known that the compensation scheme can satisfy the surrounding residents. The highlights of this paper can be described as follows: First, the analytic hierarchy process is used to comprehensively consider the pollutants, which simplifies the establishment process of the model. Second, the pollutant concentration is graded, and the concentration equivalent map is drawn to make the monitoring point layout more representative. The economic compensation plan is more reasonable and more convincing to the public.